2014
DOI: 10.5505/agri.2014.42650
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy pain: effects of the combination of incisional and intraperitoneal levobupivacaine before or after surgery

Abstract: Özet Amaç SummaryObjectives: We aimed to investigate whether the timing of administration, using a combination of incisional and intraperitoneal levobupivacaine (0.25%), has an effect on the postoperative pain after laparoscopic cholecystectomy in a prospective, randomized, and controlled study. Methods: Sixty six patients were allocated to one of the three groups. Group BS received levobupivacaine before trocar site incision and intraperitoneal levobupivacaine immediately after pneumoperitoneum. Group AS rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Administering levobupivacaine before surgery might be advantageous for less intraoperative fentanyl consumption, while levobupivacaine after surgery is advantageous for less postoperative rescue analgesic requirement. [3] Morsy at al., in his study included 80 patients scheduled for LC, divided into three groups. Group C received 50 ml normal saline intraperitoneally; Group L received 200 mg lidocaine intraperitoneally; and Group N received 10 mg nalbuphine intraperitoneally in 50 ml normal saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administering levobupivacaine before surgery might be advantageous for less intraoperative fentanyl consumption, while levobupivacaine after surgery is advantageous for less postoperative rescue analgesic requirement. [3] Morsy at al., in his study included 80 patients scheduled for LC, divided into three groups. Group C received 50 ml normal saline intraperitoneally; Group L received 200 mg lidocaine intraperitoneally; and Group N received 10 mg nalbuphine intraperitoneally in 50 ml normal saline.…”
Section: Discussionmentioning
confidence: 99%
“…This can prolong hospital stay, which is particularly of utmost importance since many centers are performing this operation as a day-case procedure. [3] Postoperative pain management remains a major challenge after laparoscopic procedures. Effective pain control encourages early ambulation, which significantly reduces the risk of deep vein thrombosis and pulmonary embolism (PE); enhances patient's ability to take deep breaths to decrease the risk of pulmonary complications (e.g., atelectasis and pneumonia); and decreases the incidence of tachycardia and unnecessary investigations related to it.…”
Section: Introductionmentioning
confidence: 99%
“…aparoscopic cholecystectomy (LC) is considered the standard technique to remove symptomatic gall bladder (1) . The pain, which happened after this technique is less and shorter than that caused by open cholecystectomy (2,3) .…”
Section: Introductionmentioning
confidence: 88%
“…The comparison in means of VAS score of pain between study groups postoperatively at abdominal level are shown in table (2). The means of VAS score after 1, 2, 4, 6, and 12 hrs.…”
Section: Vas For Abdominal Painmentioning
confidence: 99%
“…• Incisional port site hernias usually at umbilicus port [15] • Slipped gallstones in the abdominal cavity [16] • Complications of the pneumoperitoneum [17,18] • Clip migration [19] • Painful scars in port-sites [20] Discussion PCS affects approximately 10%-15% of the patients and seems to have age and sex differences. The incidence of PSC is 43% in patients aged 20 to 29 years, 27% in those aged 30 to 39 years, 21% in the 40 to 49 years group, 26% in the 50 to 59 years group and 31% among those aged 60 to 69 years; it does not seem to manifest in patients older than 70 years.…”
Section: Additional Causes Of Pcsmentioning
confidence: 99%